Biosynthesis of eco‐friendly and recyclable Pd/LDHs catalyst using the withered leaves extract for Suzuki coupling reaction. Issue 1 (3rd January 2020) - Fan, Xizheng; Zheng, Yanyan
Abstract : The hydrotalcite‐supported palladium (Pd) catalyst is prepared with a green and environmentally friendly route, introducing the extract of withered leaves as a dispersant and reducing agent (Pd/LDHs‐B). Compared with the as‐prepared catalyst (Pd/LDHs‐P with the average diameter of 4.3 nm) using a chemical synthesis method with polyvinylpyrrolidone as a dispersant and ascorbic acid (Vc) as a reductant, the results indicate that the size of Pd nanoparticles in Pd/LDHs‐B is smaller (ca. 3.6 nm). The Pd‐LHDs‐B (0.5 mmol‰) exhibits higher activity (98.66%) than Pd/LDHs‐P (98.19%) in the Suzuki reaction of 4‐bromotoluene and phenylboronic acid at 60°C for 30 min. Also, the reusability of Pd/LDHs‐B is confirmed by recycling tests without a significant decrease in activity.